2020
DOI: 10.21203/rs.2.20218/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical features, treatment, and survival outcome of primary pulmonary NUT midline carcinoma

Abstract: Objective: NUT midline carcinoma (NMC), a rare type of squamous cell carcinoma, is genetically characterised by NUT midline carcinoma family member 1 (NUTM1) gene rearrangement. NMC can arise from the lungs; however, there is no standard for the management of primary pulmonary NMC. This study aimed to confirm the clinical features and report the treatments, especially with immune checkpoint inhibitors (ICIs), and outcomes of patients with primary pulmonary NMC. Methods: A retrospective review of patients with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…A retrospective review reported seven cases of primary pulmonary NMC between 2015 and 2018. 17 Similar to the reported cases in that cohort, our patient also presented with a primary tumor in the lung. The gender and age of our patient are consistent with the demographics of that series, which showed an age range of 23-74 years and consisted of both males and females.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A retrospective review reported seven cases of primary pulmonary NMC between 2015 and 2018. 17 Similar to the reported cases in that cohort, our patient also presented with a primary tumor in the lung. The gender and age of our patient are consistent with the demographics of that series, which showed an age range of 23-74 years and consisted of both males and females.…”
Section: Discussionsupporting
confidence: 88%
“…9 However, the median survival within this retrospective review of patients with lung masses was 2.75 months, suggesting that, despite receiving multiple treatments, primary pulmonary NMC may be more aggressive than NMC located at other sites. 17 Unfortunately, our patient survived only five months following initial presentation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In another case series of five NC patients treated with ICIs, the response rate to immunotherapy could be improved by previous radiation therapy, whereas one patient with high TMB did not respond to immunotherapy (12). A further case analysis of twelve patients also supported the hypothesis that radiotherapy followed by immunotherapy results in beneficial outcomes.…”
Section: Immunotherapy In Nut Carcinomamentioning
confidence: 76%
“…However, ifosfamide-based regimens and additional radiation therapy have shown some promising results, with published cases of some very rare partial or complete responses in non-thoracic NC (6,(8)(9)(10)(11). The combination of carboplatin and paclitaxel is frequently used in thoracic NC, but with only limited success and progression free survival rates below 3 months (12)(13)(14).…”
Section: Introduction Nut Carcinomamentioning
confidence: 99%